Production of a monospecific antiserum to cathepsin L: The histochemical location of enzyme in rabbit fibroblasts. Issue 2 (February 1984) - Etherington, David J.; Mason, Robert W.; Taylor, Mark A. J.; Wardale, R. John
Abstract : A polyclonal antibody against rabbit cathepsin L was raised in goats and shown to be specific for both active and inactive enzyme. Using this antibody we have examined the distribution of cathepsin L in primary rabbit skin fibroblasts by immunohistochemistry and found that all the enzyme is located within lysosomal granules. At confluence many cathepsin-L-containing lysosomes were seen in each celt. A new but nonspecific histochemical substrate for cathepsin L was tested and a similar distribution was obtained. Our results indicate that the immunohistochemical technique can be reliably employed for the specific location of cathepsin L in cells and tissues.